2005
DOI: 10.1111/j.1600-6143.2004.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Supply of Pre- and Probiotics Reduces Bacterial Infection Rates After Liver Transplantation—A Randomized, Double-Blind Trial

Abstract: Bacterial infections frequently occur early after liver transplantation. We recently reported significant progress with a synbiotic composition, consisting of one lactic acid bacteria (LAB) and one fiber, which reduced the infection rate from 48% (with selective bowel decontamination) to 13%. Now, our aim is to study if a combination of different LAB and fibers would further improve outcome.A prospective randomized double-blind trial was undertaken in 66 liver transplant recipients. All patients received enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
276
2
13

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(298 citation statements)
references
References 21 publications
(26 reference statements)
7
276
2
13
Order By: Relevance
“…However, few of these studies included testing for digestive enzymes [65]. Other relevant studies on probiotics examined combined effects, for example, of pepsin and pH or pancreatic enzyme and bile salts [66]. Notably, well-studied probiotics were subjected to individual and multiple stress-based assays and were found to be highly resistant to bile salts and digestive enzymes under an acidic pH of 2.0 [67].…”
Section: Discussionmentioning
confidence: 99%
“…However, few of these studies included testing for digestive enzymes [65]. Other relevant studies on probiotics examined combined effects, for example, of pepsin and pH or pancreatic enzyme and bile salts [66]. Notably, well-studied probiotics were subjected to individual and multiple stress-based assays and were found to be highly resistant to bile salts and digestive enzymes under an acidic pH of 2.0 [67].…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these previous reports did not examine the changes in the gut flora that resulted from the synbiotic therapy [1][2][3][6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have described the effects of probiotics/synbiotics for general infectious complications in various patients, such as liver transplantation [1,2], major abdominal surgery [3][4][5], severe acute pancreatitis [6][7][8], trauma [9,10], and critically ill patients [11][12][13]. However, these reports generally did not examine changes in the gut flora following probiotic/synbiotic therapy [1][2][3][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…8 The use of probiotics and antibiotics has been shown to reduce bacterial translocation in a mouse model of sepsis and decrease liver injury in patients with cirrhosis. [9][10][11] Dapito et al demonstrated the efficacy of rifaximin, a nonabsorbable antibiotic already used in subjects with advanced liver disease and hepatic encephalopathy, for reducing promotion of HCC in their mouse model. It would have been interesting to explore the effect of norfloxacin in HCC promotion, considering that it is the standard antibiotic used for prevention of spontaneous bacterial peritonitis and infections in high-risk patients who have cirrhosis.…”
Section: Commentmentioning
confidence: 99%